2014
DOI: 10.1093/alcalc/agu043
|View full text |Cite|
|
Sign up to set email alerts
|

Managing Alcohol Problems in General Practice in Europe: Results from the European ODHIN Survey of General Practitioners

Abstract: The extent of alcohol education and GPs' attitudes towards alcohol were associated with the reported number of patients managed. Thus, it is worth exploring the extent to which improved education, using pharmacotherapy in primary health care and a shift to personalized health care in which individual patients are facilitated to undertake their own assessment and management (individual responsibility) might increase the number of heavy drinkers who receive feedback on their drinking and support to reduce their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 19 publications
2
71
2
5
Order By: Relevance
“…Although there have been a number of international studies examining providers’ attitudes in this field [12,13,14,15,16], as far as we are aware, there have been no published studies with repeated attitude measures that have further examined the original model of the Maudsley Alcohol Pilot Project. The European ODHIN (Optimizing delivery of health care interventions) project reported in this paper allows the opportunity to do so.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a number of international studies examining providers’ attitudes in this field [12,13,14,15,16], as far as we are aware, there have been no published studies with repeated attitude measures that have further examined the original model of the Maudsley Alcohol Pilot Project. The European ODHIN (Optimizing delivery of health care interventions) project reported in this paper allows the opportunity to do so.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear who is best placed to provide this care. Higher levels of practitioner role security and therapeutic commitment (Anderson & Clement, 1987), have been shown to be associated with the management of alcohol problems in primary care patients (Anderson et al, 2014). Our study found the DOs with whom the arrestees have the most frequent contact are adept in interpersonal interactions within this context of containment; providing credibility and skills that are considered necessary to navigate this setting.…”
Section: Discussionmentioning
confidence: 64%
“…Las cifras son similares en las categorías "no consumen" y "consumo medio". (Anderson et al, 2014;Rehm, Rehm, Shield, Gmel, & Solé, 2013).…”
Section: Resultsunclassified